Combined Application of Nitrogen and Phosphorus Promotes the Growth and Nutrient Accumulations of Cinnamomum camphora Container Seedlings - Xue Mao; Guangtao Zhang; Zemao Liu; Fenglong Huang; Fangyuan Yu (Agriculture, 2024)
Combining the application of nitrogen and phosphorus is widely recognized as an effective measure to promote seedling growth. The purpose of this study was to investigate the effects of the combined application of nitrogen and phosphorus on the growth and nutrient status of C. camphora container seedlings. Exponential fertilization was applied to a range of fertilizers, including single nitrogen fertilizer, single phosphorus fertilizer, and combinations of nitrogen and phosphorus to C. camphora. Eight distinct fertilization levels of treatment (CK, N1, N2, N3, P, N1P, N2P, and N3P) were established. The height and ground diameter of the seedlings were determined periodically in each treatment group. Biomass, root system (including root length, root surface area, and root volume), and nutrient accumulation (content of soluble sugars, soluble proteins, and starch in the root system, stems, and leaves) were determined for each treatment group of seedlings. The N3P treatment (N: 9000 mg∙plant−1 + P: 6000 mg∙plant−1) had the most significant effect on the height and ground diameter of C. camphora container seedlings, while the N3 treatment (N: 9000 mg∙plant−1) proved to be the most beneficial for biomass accumulation among the eight different fertilizer levels. In addition, a single P fertilizer (P: 6000 mg∙plant−1) emerged as the most effective fertilizer for enhancing root morphology (root length, root surface area, root volume, and root average diameter) and accumulating nutrient composition (soluble sugar, soluble protein, and starch). Furthermore, it was discovered that a high level of nitrogen fertilization hindered the accumulation of nutrient composition in C. camphora container seedlings. Our comprehensive analysis revealed that nitrogen fertilizer promoted the morphological growth of C. camphora container seedlings, while phosphorus fertilizer proved to be the most beneficial for root growth and nutrient composition accumulation. Additionally, it was emphasized that controlling the quantity of nitrogen fertilizer is also a crucial measure.